Outcomes of open, laparoscopic, and hand-assisted laparoscopic surgeries in elderly patients with right colon cancers: A case–control study. Issue 35 (August 2018) - Wei, Mingtian; Zhang, Xubing; Ma, Pingfan; He, Wanbin; Bi, Liang; Wang, Ziqiang
Abstract : Abstract: An increasing proportion of patients aged more than 70 years old are suffering from colorectal cancers. This study aimed to compare the short- and long-terms outcomes between open surgery (OS) or conventional laparoscopic surgery (LS) and hand-assisted laparoscopic surgery (HALS) in treatment of these elderly patients with right colon cancers. We retrospectively reviewed patients who underwent right colon resections for cancers in our institution between June, 2009 and December, 2014. Short- and long-terms outcomes including surgical endpoints, postsurgical recovery data, postoperative morbidity and mortality, overall survival and disease-free survival were compared among OS, LS, and HALS groups. All data were analyzed by SPSS 22.0. Finally, 69 consecutive patients (OS = 26, LS = 24, HALS = 19) with right colon cancers were included in the analysis. Compared with OS, HALS was associated with less time to first anus exhaust ( P = .013), first liquid diet ( P = .045), and first soft diet ( P = .036). Meanwhile, there were significant less operative time ( P = .0027), blood loss ( P < .001), and less time to first liquid diet ( P = .009) in HALS, compared with LS. In regards to long-term outcomes, there were no significant differences in overall survival and disease-free survival among the 3 groups. Compared with OS or LS, HALS may be more favorable in the treatment of elderly right colon cancers with decreased surgical time and postoperative recovery, and comparable cancer-specific survivals.